Optimizing English for Tourism Instruction: How Language Focus Mediates the Relationship between Content Quality and Student Learning Perception - Muhammad Arfin Muhammad Salim; Hasrul; Mohd Hilmi Hamzah (Universitas Sulawesi Barat, 2026)
Developing English teaching materials that align with industry demands remains a major challenge in English for Specific Purposes (ESP), particularly in tourism and hospitality education, where language competence directly influences professional readiness. While previous studies have emphasized instructional content, limited attention has been given to understanding the mechanisms through which content quality shapes students’ learning experiences. This study investigates the mediating role of Language Focus in the relationship between Content Focus and Student Perception using a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. Data were collected from 149 undergraduate students enrolled in tourism and hospitality programs at Makassar Tourism Polytechnic through structured questionnaires. The findings demonstrate that Content Focus significantly influences Language Focus, which subsequently enhances Student Perception. Moreover, Language Focus partially mediates the relationship between Content Focus and Student Perception, indicating that high-quality instructional content contributes to positive learning experiences primarily by strengthening learners' language development. These findings extend the theoretical understanding of ESP material design by positioning Language Focus as a key pedagogical mechanism that links instructional content to educational outcomes. Practically, the study provides evidence-based guidance for curriculum developers and educators to prioritize industry-relevant, linguistically structured, and pedagogically meaningful learning materials. The findings also support the development of competency-based English curricula that better prepare graduates for communication demands in the global tourism and hospitality workforce.